Clinical characteristics of IgG4-RD patients infected with COVID-19 in Hubei, China - Chen, Yu (Semin Arthritis Rheum, 2020)
OBJECTIVE: IgG4-related disease (IgG4-RD) is an immune-mediated multi-organ, chronic and progressive disease. Therefore, we conducted a study to investigate the susceptibility of COVID-19 in IgG4-RD patients in Hubei province, and to characterize the clinical manifestation of COVID-19 in IgG4-RD patients. METHODS: A follow-up system that includes over 200 IgG4-RD patients across the country during the past ten years. A total of ninety-one patients with IgG4-RD who live in Hubei, China were identified and responded to our survey. Medical history, clinical symptoms, laboratory tests, CT imaging, and treatment were obtained through a standardized data collection form, and then independently reviewed by two investigators. RESULTS: 2 of 91 cases were infected with COVID-19. Both of them were classified as moderate type. The symptoms such as fever and cough and radiologic features were similar to other COVID-19 patients. Neither of them episode recurrent of IgG4-RD nor progressed to severe or critical condition of COVID-19 under the condition of continuous oral low-dose of glucocorticoids. Besides, patient 2 took a long time for SARS-CoV-2 nucleic acid to turn negative. CONCLUSION: IgG4-RD patients may belongs to the susceptible population of COVID-19 infection, and thus need more careful personal protection. Early identification and properly treatment are very important to prevent IgG4-RD patients with COVID-19 from progression to severe condition.